3-D vertically aligned few layer graphene – partially reduced graphene oxide/sulfur electrodes for high performance lithium–sulfur batteries. Issue 7 (25th July 2017) - Singh, D. P.; Soin, N.; Sharma, S.; Basak, S.; Sachdeva, S.; Roy, S. S.; Zanderbergen, H. W.; McLaughlin, J. A.; Huijben, M.; Wagemaker, M.
Abstract : 3D electrodes comprising of vertically-aligned, few-layered graphene, melt impregnated with partially reduced graphene oxide/sulfur nanocomposites (3D FLG/PrGO/S) are reported for high performance (1040 mA h g −1 ) Li–S batteries. Abstract : 3-D vertically aligned few-layered graphene (FLGs) nanoflakes synthesised using microwave plasma enhanced chemical vapour deposition are melt-impregnated with partially reduced graphene oxide-sulfur (PrGO-S) nanocomposites for use in lithium–sulfur batteries. The aligned structure and the presence of interconnected micro voids/channels in the 3-D FLG/PrGO-S electrodes serves as template not only for the high sulfur loading (up to 80 wt%, areal loading of 1.2 mg cm −2 ) but also compensates for the volume changes occurring during charge–discharge cycles. The inter-connectivity of the electrode system further facilitates fast electronic and ionic transport pathways. Consequently, the binder-free 3-D FLG/PrGO-S electrodes display a high first-cycle capacity (1320 mA h g −1 at C/20), along with excellent rate capability of ∼830 mA h g −1 and 700 mA h g −1 at 2C and 5C rates, respectively. The residual functional groups of PrGO (–OH, –C–O–C– and –COOH) facilitate fast and reversible capture of Li + ions while confining the polysulfide shuttles, thus, contributing to excellent cycling capability and retention capacity. The 3D electrodes demonstrate excellent capacity retention of ∼80% (1040 mA h g −1 at C/10) over 350 charge–discharge cycles. Comparatively, the 2-D planar PrGO-S electrodes displayed poor electronic conductivity and can only provide 560 mA h g −1 after 150 cycles, thereby further highlighting the vital role of the electrode morphology in improving the electrochemical performance of Li–S batteries.